At home e-based physical exercise programs in patients with multiple sclerosis: a scoping review - Adnan, Rafl; Roikjaer, Stine Gundtoft; Samadzadeh, Sara; Richter, Camilla Josefine; Weinshenker, Brian G.; Paul, Friedemann; Skou, Søren Thorgaard; Dalgas, Ulrik; Asgari, Nasrin (Frontiers in Neurology, 2024)
Introduction Physical exercise (PE) improves symptoms and quality of life in people with multiple sclerosis (pwMS). However, incorporating PE into daily lives of pwMS pose difficulties. As an alternative to in-person PE, e-based PE has been proposed because of its advantages in terms of accessibility and convenience. Objective To synthesize existing evidence on e-based PE at home in adults MS and discuss study designs, rehabilitation programs, intervention effects and possible knowledge gaps. Methods In this scoping review, a systematic search in electronic databases including Embase, Medline, CINAHL and Cochrane Library was conducted following the PRISMA guidelines. Peer-reviewed articles in English on e-based PE interventional studies at home involving adult pwMS, published from 2008 until April 2023, were identified and exported to Covidence. Data from the included studies were extracted and synthesized. This scoping review identified different types of e-based PE interventions used in pwMS across different study designs, but when evaluating intervention effects, this review focused solely on randomized controlled trials (RCTs). Results A total of 3,006 studies were retrieved and 179 studies were screened in full text, resulting in the inclusion of 54 studies with a total of 2,359 pwMS. Of those, 33 were RCTs and three were qualitative studies. The studies reported on various e-based interventions including video-based programs, telerehabilitation, and web-based programs. The interventions evaluated muscle strength, cardiorespiratory fitness, walking speed, endurance, balance, and fatigue, as well as symptoms of depression and cognitive dysfunction. E-based PE interventions at home in RCTs demonstrated improvement of depressive symptoms and anxiety, while inconsistent results were reported for fatigue, walking speed and balance. No significant benefits were observed regarding dexterity. Results were generally heterogeneous and were limited by small sample sizes. Several limitations were identified, such as lack of physical activity assessment prior to the intervention and poor reporting of duration, intensity, frequency and adherence to e-based PE interventions. Conclusion E-based PE interventions in pwMS may improve MS-related symptoms, but the study quality is generally low, and findings are often inconsistent. Several important limitations of the existing literature have been identified in the present review, which can guide future research.